An Evaluation And Development Of Chromatographic Methods For The Study Of Chemical Profiles Of Illicit Heroin Samples. - Chhunnu Lal, Shobha Kumar; Nair, N.K.; Navaratnam, V. (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1989)
Thin Layer Chromatography . (TLC) , High Performance Liquid Chromatography (HPle) and Gas Chromatography (GC) systems were developed for separation and quantitation of the major and some of the trace opiates present in illicit heroin samples.